BASES CONCEPTUALES PARA COMPRENDER LA IMPORTANCIA DEL TERRITORIO EN LA CONFORMACIÓN DE LA IDENTIDAD: EL CASO DE SAN RAFAEL DE ESCAZÚ - Méndez, Jesús (Universidad de Costa Rica, 2013)
This article presents the importance of territory as a key component in the configuration of the identity of its inhabitants. It presents guidelines that allows appreciate the territory as the physical environment where social relations are re-produced, but above all, it lets to understand how is recognized by its occupants and outsiders as an extension of identity of group that lives there, by reference the district of San Rafael de Escazú.